2011
DOI: 10.1124/jpet.110.176990
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Is a Fast Channel Inhibitor of P2X4 Receptors

Abstract: P2X receptors (P2XRs) are ion channels gated by synaptically released ATP. The P2X4 is the most abundant P2XR subtype expressed in the central nervous system and to date is the most ethanol-sensitive. In addition, genomic findings suggest that P2X4Rs may play a role in alcohol intake/preference. However, little is known regarding how ethanol causes the inhibition of ATP-gated currents in P2X4Rs. We begin to address this issue by investigating the effects of ethanol in wild-type and mutant D331A and M336A P2X4R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…Furthermore, these receptors are localized in key brain regions associated with alcohol consumption and reinforcement, such as the ventral tegmental area (VTA) and nucleus accumbens (NAc); i.e., the mesolimbic reward pathway (Pierce et al, 2006; Xiao et al, 2008). Findings indicate that intoxicating and anesthetic ethanol (EtOH) doses desensitize the response of P2X4R-expressing cell lines to ATP exposure (Li et al, 1993; Xiong et al, 2000; Davies et al, 2005; Ostrovskaya et al, 2011), suggesting EtOH alters the effects of these receptors on modulating neurotransmission. This effect likely occurs in part at P2X4R ectodomain-transmembrane segment interfaces (Lalo et al 2007; Asatryan et al, 2008), as the inhibitory effect of EtOH on P2X4Rs may be reversed by point mutations in these areas (Popova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these receptors are localized in key brain regions associated with alcohol consumption and reinforcement, such as the ventral tegmental area (VTA) and nucleus accumbens (NAc); i.e., the mesolimbic reward pathway (Pierce et al, 2006; Xiao et al, 2008). Findings indicate that intoxicating and anesthetic ethanol (EtOH) doses desensitize the response of P2X4R-expressing cell lines to ATP exposure (Li et al, 1993; Xiong et al, 2000; Davies et al, 2005; Ostrovskaya et al, 2011), suggesting EtOH alters the effects of these receptors on modulating neurotransmission. This effect likely occurs in part at P2X4R ectodomain-transmembrane segment interfaces (Lalo et al 2007; Asatryan et al, 2008), as the inhibitory effect of EtOH on P2X4Rs may be reversed by point mutations in these areas (Popova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…P2X receptors are ubiquitously expressed ligand-gated cation channels that mediate a remarkable variety of physiological and pathophysiological reactions, especially in microglia 16-20, 26 . More recently, purinergic receptors have been implicated in alcohol abuse disorders, affecting signaling in the CNS 27, 28 . Studies have shown that alcohol acts as an allosteric regulator inhibiting P2X4R function most likely operating through interactions with the TM domains or hydrophobic regions within the channel structure 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol inhibits ATP-activated currents in rat and mouse neurons, suggesting a role for P2X4R in ethanol-related behaviors. While building evidence supports a role for P2X4R in the action of alcohol 28 , their role in modulating the functional activities of microglia is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The P2X4R and to some extent also the P2X2R are positively modulated by high concentrations of ethanol (ca. 100 mM) (Yi et al, 2009; Ostrovskaya et al, 2011). …”
Section: P2xr Modulatorsmentioning
confidence: 99%